PENGEMBANGAN LEMBAGA PENGELOLA DANA BERGULIR SYARIAH DALAM MENDUKUNG USAHA MIKRO KECIL DAN MENENGAH DI INDONESIA - Rusydiana, Aam Slamet; Nugraha, Taufik (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2018)
This study attempts to identify the factors of needs, activities and objectives in the development of revolving fund management institution (LPDB) sharia in Indonesia, using the Interpretative Structural Model (ISM) approach. The results of this study provide some conclusions include: (1) Elements of the needs of the key in LPDB sharia development strategy in Indonesia to improve SMEs is the need for strong support on internal condition of the institution; (2) Elements of activities that are key to LPDB Shariah development are to identify the problem faced by the member in the field and give some solutions, and (3) Elements of problem that maybe faced in LPDB sharia development in Indonesia is the changes on technology in business lanscape and economic, overall